Least square method for Solving Linear Fredholm and Volterra Integro – Differential Equations of the Second Kind Using Bernstein Polynomial (Journal of the College of Basic Education, 2023)
The main purpose of this paper lies briefly in submitting least square method for solving linear Fredholm and Volterra integro differential equations of the second kind with the aid of Bernstein polynomials as basic functions to compute the approximated solutions of Fredholm and Volterra integro differential equations .Two examples are given for determining the accuracy of the proposed results method.